THE INFLUENCE OF RUNNING DICTATION TECHNIQUE AND LEARNING MOTIVATION TOWARDS READING COMPREHENSION ACHIEVEMENT OF THE NINTH GRADE STUDENTS AT MTSN 1 OGAN ILIR - Purwanto Purwanto (ELTE Journal (English Languange Teaching and Education), 2019)
AbstractThis research is concerned with the influence of running dictation technique and learning motivation towards reading comprehension achievement of the ninth grade students of MTsn 1 Ogan Ilir. In this study 60 students of ninth grade students of MTsN 1 Ogan Ilir in the academic year 2018/2019 were chosen as samples by means of two stage random sampling. This study applied factorial research design. The data were collected by using questionaire and test. The data were analyzed by using Paired Sample t-test, Independent Sample t-test, and Two-Way ANOVA. The results showed that, first, there was a significant influencein students’ reading comprehension taught by using running dictaton technique. Second, there was not any significant influence in students’ reading comprehension taughtby conventional teaching technique. Third, there was significant influence in students’ reading comprehension students who have high and low learning motivation by using running dictation technique and conventional teaching technique. Last, there is not any significant interaction effects of motivation on students’ narrative text comprehension taught by using running dictation technique and learning motivation towards the students’ reading comprehension of MTsN 1 Ogan Ilir Palembang. So, running dictation technique was effective for students who have high and low learning motivation.Keywords: Running Dictation Technique, Conventional Teaching Technique, Learning Motivation, Reading Comprehension.